2021
DOI: 10.1002/ajh.26332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular predictors of fibrotic progression in essential thrombocythemia: A multicenter study involving 1607 patients

Abstract: The current retrospective study involving a total of 1607 patients was designed to identify clinical and molecular variables that were predictive of inferior myelofibrosis‐free survival (MFS) in WHO‐defined essential thrombocythemia (ET), utilizing three independent patient cohorts: University of Florence, Italy (n = 718); Mayo Clinic, USA (n = 479) and Policlinico Gemelli, Catholic University, Rome, Italy (n = 410). The Florence patient cohort was first examined to identify independent risk factors for MFS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…In particular, the association of TP53 mutations and leukemic transformation in ET is underscored 29 . A more recent study included 1607 WHO‐defined ET patients from three independent centers of excellence and showed a higher risk of fibrotic progression in patients harboring JAK2 V617F allele burden >35% and CALR type 1/like or MPL mutations 30 ; in the particular study, among the 479 cases from the Mayo Clinic, fibrotic progression was documented in 16% versus 7% at 10 years and 44% versus 25% at 20 years, in the presence versus absence of these high risk molecular markers 30 . Driver mutational status has not been shown to predict survival in ET 49 but JAK2 mutations in ET have been associated with increased risk of thrombosis, leading to the development of IPSET‐thrombosis (see below), a globally applicable risk model for thrombosis in ET 31,32 …”
Section: Essential Thrombocythemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the association of TP53 mutations and leukemic transformation in ET is underscored 29 . A more recent study included 1607 WHO‐defined ET patients from three independent centers of excellence and showed a higher risk of fibrotic progression in patients harboring JAK2 V617F allele burden >35% and CALR type 1/like or MPL mutations 30 ; in the particular study, among the 479 cases from the Mayo Clinic, fibrotic progression was documented in 16% versus 7% at 10 years and 44% versus 25% at 20 years, in the presence versus absence of these high risk molecular markers 30 . Driver mutational status has not been shown to predict survival in ET 49 but JAK2 mutations in ET have been associated with increased risk of thrombosis, leading to the development of IPSET‐thrombosis (see below), a globally applicable risk model for thrombosis in ET 31,32 …”
Section: Essential Thrombocythemiamentioning
confidence: 99%
“…As is the case with fibrotic transformation rates, blast transformation rates are also expected to be higher (2%) in younger patients due to long disease duration 47 . Integration of molecular information in risk assessment of progression to post‐ET MF (Table 3) was recently exploited 30 . Although in post‐ET MF the most frequently used treatment remains HU, an increase in the use of the JAK1/2 inhibitor ruxolitinib has to be noted 48 .…”
Section: Essential Thrombocythemiamentioning
confidence: 99%
“…Haider et al showed a high risk of fibrotic progression in MPL-positive ET [48]. Recently, type 1/type 1-like CALR and MPL were confirmed to be associated with reduced SMF-FS [49]. In the same paper, within JAK2V617F positive cases, those with AB > 35% have a higher risk of evolution [49].…”
Section: Predictive Factors Of Evolution To Post-polycythemia Vera An...mentioning
confidence: 84%
“…Recently, type 1/type 1-like CALR and MPL were confirmed to be associated with reduced SMF-FS [49]. In the same paper, within JAK2V617F positive cases, those with AB > 35% have a higher risk of evolution [49]. As for M-GVs, deep sequencing analysis showed that somatic mutations in at least one gene among SH2B3, SF3B1, TP53, IDH2, EZH2, and mostly U2AF1 were associated with shorter SMF-FS [39].…”
Section: Predictive Factors Of Evolution To Post-polycythemia Vera An...mentioning
confidence: 88%
See 1 more Smart Citation